Meshing, geometric modeling and numerical simulation 1: Form functions, triangulations and geometric modeling - Borouchaki, Houman; George, Paul L. (ISTE Ltd., 2017)
Triangulations, and more precisely meshes, are at the heart of many problems relating to a wide variety of scientific disciplines, and in particular numerical simulations of all kinds of physical phenomena. In numerical simulations, the functional spaces of approximation used to search for solutions are defined from meshes, and in this sense these meshes play a fundamental role. This strong link between the meshes and functional spaces leads us to consider advanced simulation methods in which the meshes are adapted to the behaviors of the underlying physical phenomena. This book presents the basic elements of this meshing vision.
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed November 03, 2017)
Keywords: Geometry -- Data processing; Numerical grid generation (Numerical analysis); Mathematical models; Finite element method; Triangulation; Models, Theoretical; Géométrie; Informatique; Grilles (Analyse numérique); Modèles mathématiques; Méthode des éléments finis; mathematical models; MATHEMATICS; Geometry; General; Geometry; Data processing